Analisis Parameter Fisik, Kimia, Biologi, dan Daya Dukung Lingkungan Perairan Pesisir Untuk Pengembangan Usaha Budidaya Udang Windu di Kabupaten Barru - Rustam, Rustam (Jurnal Natur Indonesia, 2010)
The regency of Barru is a potential region for Tiger prawn cultured in the South Sulawesi Province. Generally, thisaquaculture activity is based on the application of intensively cultivated pattern by using artificial feed as a sourceof the prawn foremost meal. Some research suggested that an intensive pattern of prawn cultured generatessome waste products that are significantly to affect such physical, chemical as well as biological parameters ofcoastal water condition. That the change in environmental quality of coastal water will affect commercial tigerprawn that is the role of water to support sustainable cultured through its carrying capacity. This research wasaimed to analyze physical, chemical and biological parameters of coastal water and to ensure its carrying capacityin maintaining commercially tiger prawn cultured. The results are expected to be some more valuable referencesfor the benefit of the development of tiger prawn aquaculture. The research was conducted in the coastal waterfrom June to December 2007. Observation was made in order to find out physical, chemical, and biological factorsthroughout the stations (i.e., sea, coastal, pond, estuaria and the outlet of the farm stations). To examine thephysical, chemical and biological parameter of spatial characteristic, a Principal Component Analysis (PCA) wasused. The used approaches to determine carrying capacity were based on capacity and receivance ability ofwaters and oxygen content. The results of this research show that the entirely physical and chemical parametersof coastal water of the Barru regency were exceeded that of the requirement thresholds of the total suspendedsediment (TSS) and the chemical oxygen demand (COD). A spatial distribution of physical and chemicalcharacteristics was measured high by TSS and COD, as well as the level of water turbidity, all at the outflow ofestuaria and the Outlet; meanwhile, the value of NO2, Phosphate, and NH3 substances was recorded high at thepond. A biological parameter was characterized by the existence of phytoplankton through its density and abundanceas well. Those of the Class Bacyllariophyceae was dominantly encountered to attain at the top as high as 75.2% inspecies composition, followed by Cyanophyceae 9.3% at the second, and the rest Chlorophyceae 8.9% andDyanophyceae and Euglenophyceae 5.9% and 0.7% respectively. Based on the stationed preferences, those in thecoastal, the pond, and the Outlet were dominated by Bacyllariophyceae, whereas the estuaria by Cyanophyceae.The Shannon’s index of diversity (H’) of the entirely stations was varied among 1.01 – 2.12 that the lowest one at theestuaria and the highest at the sea. The coastal water has its carrying capacity to support the excess of 506,437kg organic waste substances based on the necessity of oxygen content suspending in the water column. Therefore,the given pond is feasible to develop to reach as much as 219 Ha intensive ponds, or 481 Ha semi-intensive pondson the other way.